2021
DOI: 10.3892/ol.2021.13072
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of BAD and DAD1 as potential targets and biomarkers in cancer (Review)

Abstract: As key regulators of apoptosis, BAD and defender against apoptotic cell death 1 (DAD1) are associated with cancer initiation and progression. Multiple studies have demonstrated that BAD and DAD1 serve critical roles in several types of cancer and perform various functions, such as participating in cellular apoptosis, invasion and chemosensitivity, as well as their role in diagnostic/prognostic judgement, etc. Investigating the detailed mechanisms of the cancerous effects of the two proteins will contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…BAD and BCL-2 remain with the BCL-2 gene, and their role is to promote apoptosis. The pro-apoptotic effect of the BAD gene is realized by the formation of heterodimers between the expression products of BAD gene and BCL-2 gene with the inhibition of the anti-apoptotic effect of BCL-2 ( 77 ). BAD gene plays a regulatory role in promoting apoptosis mainly through phosphorylation of Ser112, Ser136, and Ser155 ( 78 ).…”
Section: The Structural Domains Of Bcl-2 Family Proteinsmentioning
confidence: 99%
“…BAD and BCL-2 remain with the BCL-2 gene, and their role is to promote apoptosis. The pro-apoptotic effect of the BAD gene is realized by the formation of heterodimers between the expression products of BAD gene and BCL-2 gene with the inhibition of the anti-apoptotic effect of BCL-2 ( 77 ). BAD gene plays a regulatory role in promoting apoptosis mainly through phosphorylation of Ser112, Ser136, and Ser155 ( 78 ).…”
Section: The Structural Domains Of Bcl-2 Family Proteinsmentioning
confidence: 99%
“…Previous studies have reported that the primary function of DAD1 is to negatively regulate programmed cell death and constitute the main component of oligosaccharyltransferase (OST) in the N-linked glycosylation of proteins 47 . The increased expression of DAD1 in hepatocellular carcinoma, colon cancer, small intestinal carcinoid, chronic lymphocytic leukemia, and prostate cancer indicates its great potential as a tumor treatment target of DAD1 41 . This work firstly verified the increased expression and anti-apoptotic function of DAD1 in BCa cells.…”
Section: Resultsmentioning
confidence: 99%
“…PLL was decorated with fluoroalkyl chains to form PLLF micelles, which self-assembled into non-compact NPs in aqueous solutions. Subsequently, the CRISPR-Cas9 plasmid targeting a glycosylation-associated gene DAD1, a new promising target for BCa therapy acquired through public data analyses and experimental verifications, was condensed by PLLF via electrostatic interactions to obtain stable NPs (denoted as PLLF/Cas9-sgDAD1) ( Figure 1 A ) 41 , 42 . With high cellular and mucosal penetrability, PLLF/Cas9-sgDAD1 NPs significantly downregulated the mRNA and protein levels of DAD1 in 5637 cells, resulting in cancer cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The rs8005354 is an intronic variant of the DAD1 gene. DAD1 has been identified as a regulator of apoptosis [ 21 ]. In animal model studies, deletion of DAD1 in the hamster TSBN7 cell line was shown to induce apoptosis [ 22 ], and the absence of DAD1 was associated with increased apoptosis in mice [ 23 ].…”
Section: Discussionmentioning
confidence: 99%